Nanostructures formed on carbon-based materials with different levels of crystallinity using oxygen plasma treatment - Ko, Tae-Jun; Jo, Wonjin; Lee, Heon Ju; Oh, Kyu Hwan; Moon, Myoung-Woon (ELSEVIER SCIENCE SA, 2015)
Nanostructure formation was explored for various carbon-based materials, such as diamond, carbon fiber, polyethylene terephthalate and poly (methylmethacrylate), which have different levels of crystallinity, ranging from perfect crystal to polymeric amorphous. After treatment of oxygen plasma glow discharge, the nanostructures on these carbon-based materials were found to evolve via preferential etching due to the co-deposition of metal elements sputtered from the metal cathode plate. Local islands or clusters formed by the metal co-deposition have a low etching rate compared to pristine regions on each material, resulting in anisotropic patterns on the carbon-based materials. This pattern formation mechanism was confirmed by covering the cathode or preventing the co-deposition of metallic sources with a polymeric material. Regardless of the level of crystallinity of the carbon-based materials, no patterns were observed on the surfaces covered with the polymeric material, and the surfaces were uniformly etched. It was found that the materials with low crystallinity had a high etching rate due to low carbon atom density, which thus easily formed high-aspect-ratio nanostructures for the same plasma treatment duration. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: SURFACE; TEMPLATELESS